Can intramammary infections change immunoglobulins and acute phase proteins of colostrum and transition milk in dairy goats? - Alcindo, J. F.; Vieira, D. S. [UNESP]; Braga, G. I. [UNESP]; Marinho, M. [UNESP]; Mendes, L. C.N. [UNESP]; Peiró, J. R. [UNESP]; Poló, T. S. [UNESP]; Feitosa, F. L.F. [UNESP] (FapUNIFESP (SciELO), 2022)
Proteiongram analysis is useful for the early diagnosis of intramammary infections during the period of colostrogenesis. This study aimed to evaluate the profile of total proteins, immunoglobulins, lactoferrin, and gamma-glutamyl transferase (GGT) in the colostrum of dairy goats with intramammary infections. Animals were divided in groups: GI (n=12) of goats without mammary gland infections, and GII (n=8) of goats with mammary gland infections. Intramammary infections were diagnosed using microbiological isolations and somatic cell counts (SCCs). Total protein was evaluated in the samples using SDS-PAGE shortly after parturition, and 24 and 48 hours after that event. Non-aureus Staphylococcus (NAS) were detected in all isolates. At 48 h, GII had high IgG levels and a SCC of 1660.25 × 103/mL. Levels of total protein were high in this group at 24 and 48 h. Albumin levels were high in goats with mastitis at 24 h. Overall, the IgG, lactoferrin, and albumin levels differed between animals with and without intramammary infections at M0. GGT activity was not influenced by the intramammary infection. The results of this study reinforce the importance of the proteinogram as an auxiliary tool in the diagnosis of mastitis in dairy goats
A infecção intramamária pode alterar imunoglobulinas e proteínas de fase aguda do colostro e do leite de transição de cabras leiteiras?
Keywords: Bacteria; Colostrum; Immunoglobulins; Proteins; Transition milk